OPTICAL STUDIES OF EXCITONS IN GAINAS/INP QUANTUM WELLS GROWN BY LOW-PRESSURE METAL ORGANIC VAPOR-PHASE EPITAXY - Shorthose, M; Maciel, A; Ryan, J; Scott, M; Davies, J; Moseley, A (1988)
The authors report optical studies of excitons in a GaInAs/InP multiple-quantum-well structure grown by low-pressure metal-organic vapour-phase epitaxy. Sharp n=1 heavy- and light-hole excitonic structure is observed in low-intensity absorption spectra at 4 K and room temperature. The low-temperature exciton luminescence linewidth of 5 meV and the long carrier lifetime at room temperature of 47 ns (at low excitation density) indicate the high quality of the sample. They have measured the dependence of the absorption coefficient on incident light intensity at the n=1 heavy-hole exciton and find pronounced nonlinearity with a low-intensity nonlinear absorption coefficient of 700 cm W-1 and the lowest saturation intensity yet reported for a quantum well system, 3.6 W cm-2.